The great war of Archimedes [videorecording (DVD)] - Yamazaki, Takashi, 1964-; Suda, Masaki, 1993-; Emoto, Tasuku, 1986-; Hamabe, Minami; Mita, Norifusa (Well Go USA Entertainment, 2021)
Pre-WWII, the Japanese Navy commissions the creation of impressive 'super-ship' Yamato, opposed by an admiral insisting on more battle-ready warships. Once ignored, Admiral Yamamoto recruits a math genius to uncover a suspected conspiracy.